Surgical outcome of patients with extradural hematoma at the Department of Neurosurgery in Chittagong Medical College Hospital: A study of 30 patients (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: extradural haematoma; Glasgow Coma Scale; pupillary dilatation; computerized axial tomographydoi: 10.3329/jcmcta.v19i1.3843Journal of Chittagong Medical College Teachers' Association 2008: 19(1):8-10